Abnormal response to photic stimulation in Juvenile Myoclonic Epilepsy: An EEG‐fMRI study. Issue 7 (23rd May 2014) - Bartolini, Emanuele; Pesaresi, Ilaria; Fabbri, Serena; Cecchi, Paolo; Giorgi, Filippo Sean; Sartucci, Ferdinando; Bonuccelli, Ubaldo; Cosottini, Mirco
Summary Objective Juvenile myoclonic epilepsy (JME) is a young‐onset electroclinical syndrome, characterized by myoclonic, generalized tonic–clonic, and possibly typical absence seizures. Interictal electroencephalography (EEG) displays 3–6 Hz spike/polyspike and wave pattern. Photosensitivity is common. Our aim was to explore the blood oxygen level–dependent (BOLD) response evoked by a highly provocative photic stimulus in a cohort of people with JME compared to a group of nonphotosensitive healthy controls, and to investigate the hemodynamic phenomena seen in patients with photosensitive JME. Methods We studied 13 JME patients and 18 healthy controls using EEG–functional magnetic resonance imaging (fMRI) performed during low luminance intermittent photic stimulation (IPS). The BOLD response to IPS was investigated both in JME and control groups. In photosensitive JME subjects, we also performed a dynamic evaluation of BOLD signal changes evoked by the photoparoxysmal response (PPR) in a time frame ranging from 10 s before the onset of the EEG paroxysm up until 10 s afterward. Results The IPS evoked a positive BOLD response in striate and extrastriate visual areas, which was less in JME patients than in controls. Moreover, people with JME had a reduced positive BOLD response in the frontoparietal areas and putamen but a stronger negative BOLD response in the primary sensorimotor cortex (SM1) and in cortical regions belonging to the default mode network (DMN). In JME, the dynamic evaluation of BOLD signal changes related to PPR revealed an early positive response in the putamen and SM1, followed by BOLD signal decrements in the putamen, caudate nuclei, thalami, and SM1. Significance Our results confirm the hypothesis that people with JME might have an altered interaction between the motor circuit and other neuronal networks, with prominent involvement of basal ganglia circuitry. The PPR could be a final expression of pathogenic phenomena occurring in the striato‐thalamocortical system, possibly a core feature of system epilepsy JME. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.